The Effectiveness of Microsoft Sway-Based Media on the Learning Outcome of Cultural Art Subject in the Elementary School - Muin, Awaluddin; Firdaus, Firdaus; Mawardaningsyah, Mawardaningsyah (Universitas Negeri Makassar, 2023)
The study aimed to determine student Cultural Arts learning outcomes and find significant differences in student Cultural Arts learning outcomes before and after using Microsoft Sway application media. The research design used was One-Group Pretest-Posttest Design involving 32 students. Samples are taken based on saturated sampling techniques. Data collection uses test results in the form of a pretest and posttest. The data analysis used is descriptive, hypothesis test, and gain test. The results showed that the average post-test value of 73.75 was higher than the average pretest value of 40.47. The results of the hypothesis test showed that the Sig value was <0.001, which means it is smaller than α (0.05), then H0 was rejected, which showed a significant difference in the use of Microsoft Sway application media to cultural arts learning outcomes. The average value gain was 0.5466 (52.79%). The table of n-gain criteria shows that 0.3 ≤ 0.5466 ≤ 0.7, which belongs to the medium category. This shows that using Microsoft Sway application media can effectively improve student learning outcomes.